Role of Individual Demographics on Selection of Investment Instruments in Kathmandu Valley - Poudel, Grishma (Nepalese Journal of Finance, 2025)
This study examines the investor’s preference and choices of choosing the investment instruments to make investment in Kathmandu valley. Investment instrument is selected as the dependent variable. Similarly, age, gender, education, income level, risk tolerance ability and social circle are selected as the independent variables. This study is based on primary data with 122 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors playing role on selection of investment instruments in Kathmandu valley. The study showed that age has a positive impact on selection of investment instruments. It means that increase in age leads to increase in experience which leads to high risk-taking ability. Similarly, gender has a positive impact on selection of investment instruments. It indicates that the gender play a vital role on selecting the investment instruments. Moreover, education level has a positive impact on selection of investment instruments. It means that increase in education level leads to increase in investment in financial market. Likewise, income level has a positive impact on selection of investment instruments. It shows that increase in income level leads to increase in investment. Similarly, risk tolerance ability has a positive impact on selection of investment instruments. It shows that higher the risk tolerance ability, higher would be the investment in financial market. Further, social circle has a positive impact on selection of investment instruments. It shows that higher the influence of social circle, higher would be the changes on selection of investment instruments.